Risk Assessment of Breast Cancer Through BI-RADS Category Using Digital Mammography Technique Among Symptomatic and Asymptomatic Women: Digital Mammography-Based BI-RADS Risk Assessment - Azam, Um e Roman; Rafaqat, Zunaira; Saleem, Zobia (Pakistan Journal of Health Sciences, 2025)
Breast cancer is the second leading cause of death among women globally. Risk factors include BRCA1 gene mutations, age, early menopause, and family history. Digital mammography is the gold standard for symptomatic women presenting with chest pain, lumps, nipple discharge, or skin changes, while asymptomatic women undergo routine screening from age 45. Risk assessment is based on correlating BI-RADS findings with patient history and socioeconomic factors. Objectives: To assess breast cancer risk through BI-RADS categories using digital mammography among symptomatic and asymptomatic women. Methods: This comparative cross-sectional study included 384 women aged 15–75 years. Data were collected using a structured questionnaire covering demographics, lifestyle, reproductive history, family cancer history, breast tissue density, and BI-RADS category. Non-probability convenience sampling was used, and analysis was performed via IBM SPSS version 26.0. Results: Most participants were aged 46–65 years, housewives, and postmenopausal. Moderate physical activity (59%), symptoms (80.3%), and prior screening mammography (61.3%) were common. While 88.1% performed self-examinations and 82.1% had professional exams, 53.2% had never undergone a mammogram. Family history of breast cancer (34.3%) was notable. Scattered fibro-glandular breast tissue predominated. Awareness of BI-RADS (43.1%) and digital mammography (62.1%) was limited. Most had no prior cancer treatment (77.4%) or radiation exposure (92.7%), with 29.9% diagnosed with breast cancer. Conclusions: Menstrual changes and early post-menopause influenced malignancy risk, with increasing age being a significant factor. Higher parity correlated with benign categories.